Compressive Strength of Paver Block Using Rubber Tyre Waste and Bamboo Fibre Under Extreme Conditions - Tuan Noor Hasanah Tuan Ismail; Avelin Grace Chandra Bose; Noor Khazanah A Rahman; Chan Chee Ming; Hazri Mokhtar; Nur Faezah Yahya; Suraya Hani Adnan (Journal of Advanced Industrial Technology and Application, 2024)
The utilisation of by-products in paver block production has gained significant attention due to its potential in environmental condition. This research investigates the effect of incorporating rubber tyre waste and bamboo fibre into the fabrication of paver block on compressive strength, water absorption, density and ultrasonic pulse velocity tests. This research comprises two batches of paver blocks fabrications following a 1:2:3 ratio (cement: fine aggregate: coarse aggregate). Batch 1 involves the fabrication of paver blocks by incorporating varying percentages of rubber tyre waste (0, 10, 20, 30, 40 and 50%), which replace a portion of the sand (referred to as rubber paver block). In Batch 2, various dosages of bamboo fibre, used as a reinforcement material were added to the paver block containing 40% rubber tyre waste, which are referred to as rubber-bamboo fibre paver blocks. Nevertheless, the compressive strength of the rubber-bamboo fibre paver blocks was further examined under two simulated environmental conditions: (1) air and dry cycle, and (2) wet and dry conditions. These conditions aim to assess the block’s resistance to temperature fluctuations, moisture effects, and their overall durability. The strength of the paver blocks decreases with the additional inclusion of rubber tyre waste. While the utilisation of 0.3% bamboo fibre has shown improvement in its strength performance compared to 0.2% and 0.4%. It suitable to used for non-loading structural applications that require strength below 25 kPa. This study was able to promote sustainable and green construction materials for paving applications through the efficient recycling of waste materials. It aligns with Sustainable Development Goals (SDG) 9 (Industry, Innovation, and Infrastructure) and 11 (Sustainable Cities and Communities).